Breastfeeding duration and eating behavior in early childhood: a systematic review - Barbara Cristina Ergang; Gabriele Luiza Caprara; Mirian Benites Machado; Paula Ruffoni Moreira; Martine Elizabeth Kienzle Hagen; Juliana Rombaldi Bernardi (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to analyze the influence of breastfeeding duration on eating behavior in children aged two to six years. Methods: this review was conducted by PRISMA guidelines. SciELO, Lilacs, Embase, and PubMed databases were researched by using a specific syntax, for studies published from 2000 to 2020. The Joanna Briggs Institute Critical Appraisal checklist was used to assess the risk of study bias. Results: a total of 26,211 articles were identified, of which seven were included in the study. The results showed a significant association in four studies. All authors used their own questionnaires to assess breastfeeding exposure; there was no standard classification of exclusive and total breastfeeding duration. The breastfeeding duration was associated with reduced food neophobia, lower scores on the food responsiveness subscale, and lower 'picky eating' behavior. Validated instruments were predominantly used to assess the outcome of eating behavior; however, this assessment was not similar between studies. Conclusion: a significant association was observed between breastfeeding duration and eating behavior in children aged two to six years. Further research should be conducted to describe the mechanisms involved in this association.